Procedures & theory for administrative. - Fulton-Calkins, Patsy, 1934-; Stultz, Karin M., jt. aut. (Mason, Ohio : Thomson/South-Western, 2004)
Includes bibliographical references and index.
Rev. ed. of: Procedures for the office. (Student CD included)
BSBA
Keywords: Office practice; Secretaries